Perspectivas da substituição gradual de termelétricas a combustíveis fósseis por sistemas fotovoltaicos em microgeração distribuída - Caldas, Leonardo Araújo (2017)
The Brazilian electrical matrix is hydrothermal, composed predominantly by hydroelectric plants and fossil fuels thermoelectric plants. Due to the water crisis experienced from 2012, the government opted for a greater participation of the fossil thermal energy in the matrix to supply the deficit of hydropower, in order to avoid a future rationing of electric energy. The energy became more expensive to consumers and Brazilian matrix became less renewable due to this fact, exposing the vulnerability of the matrix and proving the need for diversification. Photovoltaic solar energy appears as a potential solution to complement this matrix in order to conserve it mostly renewable. In the present work, environmental and economic-financial analysis of grid-connected photovoltaic systems in distributed generation were performed in order to compare them with the fossil thermals of the Brazilian electrical matrix. The environmental analysis was performed through Life Cycle Assessment (LCA) in order to quantify, in kgCO2eq, greenhouse gases (GHG) emissions associated to the production of 1 MWh of distributed generation photovoltaic systems and compare to fossil thermals of the Brazilian electrical matrix. The assessment of distributed generation photovoltaic systems allowed us to identify that the phases of higher GHG emissions are: production of the components of the photovoltaic modules and generation of electricity demanded to produce them. Together they account for 72.75 %, in the case of polycrystalline silicon technology, and 74.21% for monocrystalline silicon, of total emissions. While in the fossil fuels thermoelectric generation the greatest impact is on the operation phase, accounting for 96.97% for coal, 96.54% for lignite, 89.29% for open cycle natural gas, 88.65% for natural gas in combined cycle, and 86.65% for oil, of GHG total emissions. The economic-financial analysis was performed using the tools: Net Present Value (NPV), Internal Rate of Return (IRR), Discounted Payback and LCOE. The analysis was performed for the 23 Brazilian capitals that are part of the ICMS Agreement 16/2015 that allows ICMS to be charged only on the net energy of the consumer unit, making the investment more attractive. The grid parity was also calculated and compared with costs associated to fossil thermal generation. It was observed that the investment is feasible for all scenarios analyzed in all capitals except Boa Vista in scenarios below and equal to the projected inflation. Tariff parity is already a reality in 20 capitals analyzed and the average discounted payback for the capitals was attractive, taking into account the life of the project.